The impact of polypharmacy and oral nutritional supplementation on nutritional status in patients residing in a long-term care facility - Ścisło, Lucyna; Pluta, Judyta; Kliś-Kalinowska, Anna; Górski, Michał; Buczkowska, Marta (Frontiers in Nutrition, 2025)
IntroductionNutritional disorders and polypharmacy are among the most important problems facing the older adults in long-term care facilities. Polypharmacy negatively affects the nutritional status of the older adults. The use of specific drugs should be evaluated on a case-by-case basis, and a new drug should be introduced with caution. The supply of medications, especially among the older adults, needs more attention and analysis of their effects on nutritional status to avoid potentially dangerous consequences. The purpose of the study was to assess the nutritional status and determine the relationship between the pharmacotherapy used and the nutritional status of patients residing in a long-term care facility.MethodsThe prospective, interventional study with a pre-post design, incorporating a retrospective study included 110 patients residing in a long-term care facility. Nutritional status was assessed before and after the nutritional intervention, which consisted of administering oral nutritional supplements (ONS). The study used the Mini Nutritional Assessment scale, body mass index (BMI), prealbumin, albumin, transferrin, and total lymphocyte count (TLC).ResultsStudies conducted have shown malnutrition in a significant group of patients. The ONS used improved the assessed parameters of nutritional status. Multivariate regression analysis showed that the incidence of malnutrition is significantly influenced by variables such as gender, age, and polypharmacy. Polypharmacy negatively correlates with nutritional status.DiscussionThere is an urgent need to improve nutrition practice and individual assessment of evidence-based pharmacotherapy use among older people, which is crucial to improving the quality of care provided.